Pertumbuhan Kembali Asystasia gangetica Pasca Aplikasi Growth Hormone pada Stek di Naungan yang Berbeda - N R Kumalasari; F M Abdillah; L Khotijah; L Abdullah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
Asystasia gangetica is one of the plantation weeds that grows under shading area and has potential use as forage. The aim of this experiment was to analyze the cutting stem of A. gangetica regrowth that immersed on growth promotor hormone under different plant shadding. The treatments were arranged A. gangetica plant in a Completely Randomized Block design that consisted of 2 hormone (auxin and cytokinin) and 5 shading (green house, open space, under Indigofera zollingeriana tree, under Bauhinia sp tree and Glyricidia sepium tree). The results showed that residual hormones have small effect on the number of A. gangetica primary branches only. Shading environment increased A. gangetica regrowth, especially on plant height, number of branches and flower development, except Bauhinia shading. It concluded that A. gangetica has potential to develop as ruminant forage due to high regrowth capability. Keywords: Asystasia gangetica, hormone residu, plant regrowth, plant shading